Acanthaceae endémicas del Perú - León, Blanca (2006)
The Acanthaceae are represented in Peru by 41 genera and approximately 275 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), basically shrubs and herbs. Here we recognize 42 endemic taxa in 15 genera. Three genera, Cephalacanthus, Orophochilus and Trichosanchezia, are endemic to Peru. Most endemic Acanthaceae are found in the Very Humid Montane and Humid Lowland Amazonian Forests regions, between 100 and 2870 m elevation. Seven endemic species are represented within Peru’s protected areas system.